2022
DOI: 10.1007/s00382-022-06471-2
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of simulated mesoscale convective systems over East Asia to the treatment of convection in a high-resolution GCM

Abstract: Mesoscale convective systems (MCSs) downstream of the Tibetan Plateau (TP) exhibit unique precipitation features. These MCSs can have damaging impacts and there is a critical need for improving the representation of MCSs in numerical models. However, most global climate models are typically run at resolutions that are too coarse to reasonably resolve MCSs, and it is still unclear how well higher-resolution global models can reproduce the precipitation characteristics of MCSs. In this study, the sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…With grid spacings of a few kilometers, CPMs can explicitly resolve deep convection, offering the potential for more reliable climate simulations (Bauer et al., 2021; Slingo et al., 2022; Stevens et al., 2019). Many studies have found that CPMs have better performance in simulating many aspects of MCSs, such as duration, propagation, and heavy precipitation (e.g., Ban et al., 2014; X. Chen et al., 2021; Feng et al., 2018; Gao et al., 2017; Li et al., 2023; Na et al., 2022; Prein et al., 2017, 2024; Zhang et al., 2021). However, these studies mostly investigated MCSs regionally using simulations from one or two CPMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With grid spacings of a few kilometers, CPMs can explicitly resolve deep convection, offering the potential for more reliable climate simulations (Bauer et al., 2021; Slingo et al., 2022; Stevens et al., 2019). Many studies have found that CPMs have better performance in simulating many aspects of MCSs, such as duration, propagation, and heavy precipitation (e.g., Ban et al., 2014; X. Chen et al., 2021; Feng et al., 2018; Gao et al., 2017; Li et al., 2023; Na et al., 2022; Prein et al., 2017, 2024; Zhang et al., 2021). However, these studies mostly investigated MCSs regionally using simulations from one or two CPMs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that CPMs have better performance in simulating many aspects of MCSs, such as duration, propagation, and heavy precipitation (e.g., Ban et al, 2014;X. Chen et al, 2021;Feng et al, 2018;Gao et al, 2017;Li et al, 2023;Na et al, 2022;Prein et al, 2017Prein et al, , 2024Zhang et al, 2021). However, these studies mostly investigated MCSs regionally using simulations from one or two CPMs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, convection‐permitting models (CPMs) have flourished due to the dramatic improvements in computer performance, making it possible to explicitly simulate convection on a large scale and over long periods of time. These models have been shown to outperform traditional convection‐parameterized models (CParMs) in accurately simulating the properties of MCSs and their related environments (Li et al., 2022; Prein et al., 2017; Yun et al., 2020). For example, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, convection-permitting models (CPMs) have flourished due to the dramatic improvements in computer performance, making it possible to explicitly simulate convection on a large scale and over long periods of time. These models have been shown to outperform traditional convection-parameterized models (CParMs) in accurately simulating the properties of MCSs and their related environments (Li et al, 2022;Prein et al, 2017;Yun et al, 2020). For example, Zhang et al (2013) investigated the causes of the Beijing extreme rainfall of 21 July 2012, which was triggered by a prolonged MCS event, and concluded that the simulation using CPMs was critical to capture the details of the complex meteorological and hydrological processes.…”
mentioning
confidence: 99%